(untitled) (CAHIERS MAGELLANES-NS, 2024)
Background: Gestational diabetes mellitus (GDM) has been an ongoing issue in Saudi Arabia. (GDM) is a condition characterized by impaired glucose tolerance that develops during pregnancy. (GDM) is a common disease affecting pregnant females, and it carries a major risk of short and long-term health problems for both mothers and their children. Gestational diabetes affects both present and future pregnancies. Multiple factors contribute to the risk of (GDM) such as advanced maternal age, obesity, and unhealthy lifestyle. The knowledge of (GDM) among women differs across different nations. Designing successful healthcare plans and strategies requires a complete understanding of the awareness level among the population. The public awareness of diabetes is necessary to provide effective educational and preventive strategies. This study aimed to evaluate knowledge and awareness levels among married females regarding the maternal and neonatal outcomes of gestational diabetes mellitus (GDM) in Saudi Arabia. Methods: An observational cross-sectional study was conducted between July 2024 – November 2024. Data were collected through a self-administered questionnaire that was designed and tested for validity and reliability and consisted of 54 questions asking about the socio-demographic characteristics, Awareness and Knowledge about GDM in general, knowledge about risk factors, and Maternal and Neonatal Outcomes of GDM, along with questions to measure personal experience, attitudes, and preferable learning methods. This study included married females in Saudi Arabia willing to participate, of reproductive age (18-45), planning or already pregnant, and those who refused were excluded. The minimum target sample size of 384 was calculated using a formula based on prevalence estimation, 95% confidence level, and 5% acceptable error. Statistical Product and Service Solutions (SPSS, version 23; IBM SPSS Statistics for Windows, Armonk, NY) was used for statistical analysis. Results: Regarding the participants’ knowledge about gestational diabetes maternal and neonatal outcomes, 87.2% out of 514 acknowledge the negative impact of gestational diabetes on maternal health. While 72.0% are aware of its link to type 2 diabetes and 55.1% recognize the risk of preeclampsia, many express uncertainties regarding these long-term risks. Additionally, 77.6% identify potential adverse effects on neonatal health, but substantial numbers remain unsure about specific issues like low blood sugar levels and future obesity risks. Regarding the score results of awareness, knowledge, and attitudes towards GDM, 60.1% displayed high awareness, while 26.3% had moderate awareness, and 13.6% showed low awareness. Knowledge levels revealed 56.6% had low knowledge, 24.1% moderate, and only 19.3% high understanding. Regarding attitudes, 66.7% expressed high concern, 27.8% moderate attitudes, and only 5.4% exhibited low recognition of risks, highlighting the need for educational interventions to improve knowledge about GDM outcomes. Conclusion: While a significant majority recognize the negative impact of GDM on maternal health, with startlingly low knowledge levels observed. These findings underscore the urgent need for targeted educational interventions to improve awareness and knowledge about the risks and management of GDM, particularly its long-term consequences such as the link to type 2 diabetes and neonatal health issues. With the prevalence of GDM estimated between 8.9% and 12.5% in Saudi Arabia.